Combating Disinformation and Misinformation through Source Identification and Tracking - Ohwadua, Emmanuel (International Journal of Science, Technology & Management, 2024)
In the social media or online networks, the posting and sharing of misleading information or fake news, is done on the fly, but difficult to reverse or control, and worse still, the purveyor of such information is difficult to identify or track; unlike traditional print or electronic media whose authors are well known and can be held responsible for any harm that the information may cause. With disinformation, misinformation and mal-information spreading at the click of a button and at breakneck speed, tech companies are struggling to regulate it on social media, while grappling with public responsibility, definitions of free speech or freedom of expression, and identification of such content and its source. This research piece has provided another prism by which the excesses of the purveyors of disinformation, misinformation and mal-information, otherwise known as fake news, propaganda or misleading information can be curtailed. In the social media platform, the author of content is elusive and may not be known because the content or material does not contain any identification that could help to identify the perpetuator, and even if eventually he/she is finally tracked – probably after the content may have been shared (say) a million times, the harm may have been done. So, the goal of this scheme is to discourage and prevent the creation and posting of harmful material on social media since such content will carry the identification of the author. The identification details of the author of content is acquired at the point of posting the content online on any social media platform, while the integrity of the content is preserved by the use of cryptographic hash function. Fundamentally, this tool, if adopted and implemented by social media platforms, it will shift the focus of the fight against fake news from regulation to prevention and control.